Digital humanities : history and development - Le Deuff, Olivier (London, UK : ISTE, Ltd. : Wiley, 2018)
Where do the digital humanities really come from' Are they really news' What are the theoretical and technical influences that participate in this scientific field that arouses interest and questions' This book tries to show and explain the main theories and methods that have allowed their current constitution. The aim of the book is to propose a new way to understand the history of digital humanities in a broader perspective than the classic history with the project of Robert Busa. The short digital humanities perspective neglects lots of actors and disciplines. The book tries to show the importance of other fields than humanities computing like scientometry, infometry, econometry, mathematical linguistics, geography and documentation.
The Republics of Letters: the Need to Communicate and Exchange -- The Science of Writings and Documentation -- From Lists to Tables, the Question of Indexing -- The Need to Find Information -- The Researcher's Workstation and the History of Hypertexts -- The Quantitative Leap: Social Sciences and Statistics -- Automatic Processing: Concordances, Occurrences and Other Interpretation and Visualization Matrices -- Metadata Systems -- The New Metrics: From Scientometrics to Webometrics -- The Map: More than the Territory -- Conclusion: A Steampunk History and an Archaeology of the (New) Media.
Online resource; title from PDF title page (EBSCO, viewed April 23, 2018).
Includes bibliographical references and index.
Keywords: Digital humanities; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Digital humanities; Digital Humanities; Geschichte; Electronic books